Increased Small Dense LDL and Decreased Paraoxonase Enzyme Activity Reveals Formation of an Atherogenic Risk in Streptozotocin-Induced Diabetic Guinea Pigs - Mutay Aslan; Filiz Ozcan; Ertan Kucuksayan (Journal of Diabetes Research)
This study aimed to investigate LDL subfraction distribution as well as serum cholesteryl ester transfer protein (CETP), lecithin-cholesterol acyltransferase (LCAT), and paraoxonase (PON1) activity in streptozotocin-induced diabetic guinea pigs. Materials/Methods. Guinea pigs were given a single intraperitoneal (ip) injection of streptozotocin (STZ) and animals having fasting blood glucose levels greater than 200 mg/dl, were considered diabetic. Protein levels of LCAT and CETP were determined via ELISA. Paraoxonase activity was measured kinetically by the formation of phenol while LDL subfraction analysis was done by disc polyacrylamide gel electrophoresis. Results. Plasma glucose and high-density lipoprotein (HDL) cholesterol were significantly increased while total cholesterol and LDL cholesterol were significantly decreased in diabetic guinea pigs compared to controls. LDL subfraction analysis revealed a significant decrease in nonatherogenic LDL-2 subfraction and a significant increase in atherogenic LDL-4 subfraction in diabetic guinea pigs compared to controls. Plasma CETP and PON1 levels were significantly decreased while LCAT showed no significant difference in diabetic guinea pigs compared to controls. Conclusion. Decreased non-atherogenic LDL-1, LDL-2 subfractions, increased small dense LDL-4 subfraction, and decreased PON1 activity, reveals formation of an atherogenic risk in diabetic guinea pigs. Decrease in CETP levels supports the observed increase in HDL cholesterol levels in diabetic guinea pigs.